JAPAN AND WATER RESOURCES OF TAJIKISTAN: CONTRIBUTION, CHALLENGES, AND REALITIES - USMONOV, Farrukh; INAGAKI, Fumiaki (CENTRAL ASIA AND THE CAUCASUS, 2017)
Here is the plain text without formatting:Global population growth increases the demand for water. The rational usage of water and efficient management are vital in various regions, including Central Asia. The Tajikistan Government also takes this matter seriously and has designated the importance of water in the National Development Strategy 2030. The progress in the water sector may impact human life and improve the living standard of the population. In this aspect, the Government of Tajikistan proposed to pay particular attention to the water issue and contribute to raising it globally. Japan is greatly concerned over the increasingly severe water problems in the world, including issues of water hygiene. It has been implementing water projects in Tajikistan starting from the early years of Tajikistan’s independence. Japan’s attention to the water crisis in the Central Asian region has increased because of the shrinking of the Aral Sea, the melting of glaciers, and the possibility of water usage of the Sarez Lake in Tajikistan. The Japanese authorities also understand the reasons for the confrontation among the states of the region over the water issue.This paper focuses on the impact of the water sector on the development of Tajikistan. It also discusses the contribution of Japan to the water sector of Tajikistan, while exploring the challenges faced and obstacles met by the projects being implemented.